Breast Cancer Review: A molecular Prospective on Diagnosis and Treatment - Haripriya, K.; Nandini, K.; Mamatha, D.M.; kumari, K Swetha (Journal of Neonatal Surgery, 2025)
Breast cancer remains a formidable global health challenge, affecting countless lives and necessitating the ongoing research to enhance understanding and treatment strategies. This article presents a comprehensive review of recent updates in breast cancer research, emphasizing the molecular perspective and advancements in diagnostics, treatment modalities, and personalized care approaches. The landscape of breast cancer diagnostics has evolved significantly, with the integration of genomic profiling, liquid biopsies, and advanced imaging techniques. These innovations enable early detection, risk assessment, and the identification of molecular subtypes, thereby facilitating tailored treatment plans and improved prognoses. Advancements in treatment modalities highlight the increasing role of targeted therapies, immunotherapies, and precision medicine. The emergence of novel drugs, coupled with an enhanced understanding of Tumor biology, offers renewed hope in mitigating drug resistance and enhancing patient outcomes. Personalized care strategies have gained prominence, with a focus on patient-centric approaches that consider genetic, environmental, and lifestyle factors. Tailoring treatment regimens to individual patient profiles optimizes efficacy while minimizing adverse effects, leading to improved quality of life. Furthermore, recent updates encompass the integration of multidisciplinary care models, innovative clinical trial designs, and the growing importance of patient advocacy. These elements converge to create a holistic framework that addresses not only the biological aspects of breast cancer but also the psychosocial and supportive care needs of patients. This review delves into the dynamic landscape of breast cancer research, highlighting recent updates that span diagnostics, treatments, and patient-centred approaches. By synthesizing these advancements, this article contributes to the dissemination of knowledge and the pursuit of more effective strategies in combatting breast cancer, fostering optimism in the ongoing fight against this complex disease